No relevant midbrain atrophy in Parkinson's disease - Elina Mäkinen; Juho Joutsa; Juuso Isotalo; Valtteri Kaasinen (WILEY-BLACKWELL, 2022)
Aims of the study - To investigate whether significant midbrain atrophy is present in Parkinson's disease (PD), and if so, whether it can be used as a marker of striatal dopaminergic degeneration. Methods - In total, 150 PD patients and 155 controls were scanned with both brain dopamine transporter (DAT) [I-123]FP-CIT SPECT and 1.5T MRI. Midbrain atrophy was measured from sagittal MRIs using the midbrain-to-pons ratios. Both striatal region-of-interest-based (Brass) and striatal and extrastriatal voxel-by-voxel-based DAT binding (SPM8) were investigated in relation to midbrain atrophy. Results - The midbrain-to-pons ratios in PD patients were slightly lower than those in the controls (mean 0.59 vs 0.61, P < 0.05). The ratios did not significantly correlate with striatal or extrastriatal [I-123] FP-CIT uptake in controls or patients with PD. Conclusions - Mild midbrain atrophy is present in PD and can be detected with MRI. However, the midbrain atrophy in PD is not associated with the level of striatal dopaminergic dysfunction, and midbrain measurements therefore cannot be used as a clinically useful predictor of dopamine function.